Given that f(x) = 2x + 1 and g(x) = 3x-1/2 solve for g(f(3))

Algebra
Tutor: None Selected Time limit: 1 Day

Jun 16th, 2015

g (f(3)) = [ 3(2x+1) -1]/2

          = (6x+2)/2 

          = 3x+1

          = (3*3) +1

          = 10

Please let me know if you have any questions and best me if you are satisfactory.


Please let me know if you need any clarification. I'm always happy to answer your questions.
Jun 16th, 2015

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Jun 16th, 2015
...
Jun 16th, 2015
Feb 21st, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer